Necesidad de tratamiento periodontal en los estudiantes de la Universidad Nacional de Loja, modalidad de estudios presencial, sexo femenino, periodo mayo-julio del 2014 - Cuenca Enríquez, María Lourdes (2014)
The present thesis had like objectives: To determine the need for treatment periodontal applying the index of the CPITN in the students of the National University of Loja form, feminine sex, period May - July, 2014; to evaluate the condition periodontal according to the Index of Need for Treatment Periodontal (CPITN); to determine the affectation grade periodontal, applying the illness index periodontal of Ramfjord. The materials and methods that were used were: the index CPITN that can be applied in a big community, using the probe WHO and the index periodontal of Ramfjord For the securing of the information one examined the students and their registered this information in the Case history periodontal which contains all the parameters to be evaluated. In the results obtained on the grade of affectation periodontal, 221 persons who represent 49 % are healthy; 137 with 30 % present light inflammatory changes to moderated that do not spread about the whole tooth; 93 persons with 21 % present gingivitis set sail to moderate; 1 person with a percentage of 0,2 % presents intense Gingivitis; as for the loss of insertion: 388 students with 86 % are healthy, 61 with 13 % do not present major 3 mm bags, 1 person with 0.2 % presents bag, from 3 to 6 mm and none of the persons presents major 6 mm bags). With what we proceed to evaluate the need for treatment periodontal that it indicates, 225 (50 %) does not need treatment periodontal, 147 (33 %) needs to improve the mouth hygiene, 78 (17 %) needs curettage, elimination of imperfect restorations and of improving the mouth hygiene, and only 2 (0.4 %) needs a complex treatment. Coming to the conclusion that most of the students present a healthy Periodontic or he needs instruction of Oral Hygiene and only minority needs curettage, elimination of imperfect restorations or a complex treatment. Key words: Periodontal treatment, Need for treatment, periodontal Affectation, CPITN, IEP